1983
DOI: 10.1128/aac.23.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tolerance of N-formimidoyl thienamycin (MK0787) in humans

Abstract: The pharmacokinetics of intravenously administered N-formimidoyl thienamycin (MK0787) were studied in 14 healthy male subjects in a single-dose study, in which the volunteers received N-formimidoyl thienamycin with and without probenecid, and in a multiple-dose study, in which the subjects were given 250 or 500 mg every 8 h for 10 doses. High dose-related plasma concentrations of Nformimidoyl thienamycin were achieved; co-administration with probenecid resulted in only minor increases in these concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 11 publications
2
28
1
Order By: Relevance
“…In addition, over the three dosage schedules studied, a linear relationship was observed between drug dose and AUC (Table 4). Both of these findings have been reported previously in unaffected adults (17,18). A total of 50 and 78% of the administered doses of imipenem and cilastatin, respectively, were recovered in the urine over the 6-h study period (Fig.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…In addition, over the three dosage schedules studied, a linear relationship was observed between drug dose and AUC (Table 4). Both of these findings have been reported previously in unaffected adults (17,18). A total of 50 and 78% of the administered doses of imipenem and cilastatin, respectively, were recovered in the urine over the 6-h study period (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Arvidsson and colleagues (1), in are similar to imipenem profiles observed in unaffected adult assessing the urinary clearance of cefsulodin in cystic fivolunteers (18). Norrby et al (17,18) have shown that the brosis patients and unaffected individuals, found comparable coadministration of either probenecid or dehydropeptidase results, although the actual renal elimination pathway(s) was inhibitors only mildly affect the systemic biodisposition of different in patients with cystic fibrosis. imipenem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, antibiotics with poor anaerobic activity, like ceftazidime (7,8,23) and aztreonam (13,25,35), or with low concentrations in the G.I. contents, like imipenem (22,26,27), were associated with smaller increases in the yeast flora of the gut.…”
Section: Discussionmentioning
confidence: 99%